2006
DOI: 10.1158/1078-0432.ccr-05-2763
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Drug Sensitivity Predicts Response and Survival after Individualized Sensitivity-Directed Chemotherapy in Metastatic Melanoma: A Multicenter Phase II Trial of the Dermatologic Cooperative Oncology Group

Abstract: Purpose: In vitro sensitivity assays are promising tools to predict the individual outcome of different chemotherapy regimens. However, a direct association between in vitro and in vivo chemosensitivity has to be shown by clinical studies. This multicenter phase II trial was aimed to investigate the efficacy of a sensitivity-directed, first-line chemotherapy in metastasized melanoma patients, and to prove an association between in vitro sensitivity and therapy outcome. Patients and Methods: The primary study e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
77
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 29 publications
0
77
2
6
Order By: Relevance
“…However, recent preclinical studies on the chemosensitivity of metastatic melanoma cells to cytotoxic agents identified high sensitivity to cytotoxic single agents including cisplatin, treosulfan, gemcitabine, as well as to combinations of gemcitabine plus treosulfan and gemcitabine plus cisplatin (Cree et al, 1999;Ugurel et al, 2003Ugurel et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent preclinical studies on the chemosensitivity of metastatic melanoma cells to cytotoxic agents identified high sensitivity to cytotoxic single agents including cisplatin, treosulfan, gemcitabine, as well as to combinations of gemcitabine plus treosulfan and gemcitabine plus cisplatin (Cree et al, 1999;Ugurel et al, 2003Ugurel et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Primary human pancreatic cancer cells were isolated and ATP-TCA was performed as described previously (Andreotti et al, 1995;Ugurel et al, 2006). Briefly, 10 000 -20 000 tumour cells per well were seeded in tumour cell-supporting growth medium in 96-well microtiter plates.…”
Section: Chemosensitivity Testing Using the Atp-tca Testmentioning
confidence: 99%
“…Various types of assays have been tested in a variety of malignancies, but none so far has been evaluated in large-scale randomised clinical trials. In this study, we used the ATP-based tumour chemosensitivity assay (ATP-TCA), which has been shown to be very sensitive and highly reproducible, at a low rate of failure (Andreotti et al, 1995;Ugurel et al, 2006).…”
mentioning
confidence: 99%
“…Conventional screening of chemotherapeutics uses an established panel of cancer cell lines (18) that have been derived from bulk tumors. A recently developed clinical approach involves performing in vitro chemosensitivity testing of tumor biopsy specimens to individualize treatment (19,20). Unfortunately, benefits have been limited, with poor correlations between bulk tumor cell sensitivity and clinical efficacy.…”
mentioning
confidence: 99%